2017
DOI: 10.1108/ijebr-03-2017-0100
|View full text |Cite
|
Sign up to set email alerts
|

Does public sector crowd out entrepreneurship? Evidence from the EU regions

Abstract: Purpose The decision to engage in entrepreneurial activities is grounded in personal characteristics (motivation) and external environmental factors. One of the main external factors might be the structure of the regional economic activity. Does a high share of the public sector affect positively regional entrepreneurship or vice versa? Does the diversity in regional economic activity is conducive for entrepreneurial development or the regional comparative advantage as expressed by spatial economies of scale o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 63 publications
(79 reference statements)
0
9
0
Order By: Relevance
“…Under public choice theory, less (government regulation) is more, as demonstrated by Aidis et al (2012) who showed that entrepreneurial entry is inversely related to the size of government, and Branstetter et al (2014) who studied how regulatory reform in Portugal stimulated entrepreneurial entry. Over and above the effect of regulation, a case can also be made that the sheer size of the public sector may crowd out the development of a vibrant entrepreneurial ecosystem (Zikou et al 2018).…”
Section: Government E-government and Entrepreneurshipmentioning
confidence: 99%
“…Under public choice theory, less (government regulation) is more, as demonstrated by Aidis et al (2012) who showed that entrepreneurial entry is inversely related to the size of government, and Branstetter et al (2014) who studied how regulatory reform in Portugal stimulated entrepreneurial entry. Over and above the effect of regulation, a case can also be made that the sheer size of the public sector may crowd out the development of a vibrant entrepreneurial ecosystem (Zikou et al 2018).…”
Section: Government E-government and Entrepreneurshipmentioning
confidence: 99%
“…The General theory of business modelling analyses risks identification and the ability of organizations to invest in those risk and rape future benefits (Marie, 2016;Xu & Carey, 2015). PE research themes A comprehensive analysis of the 61 PE articles reviewed for this study revealed that they could be classified into three distinct themes: 1) Efficiency in PE (e.g., Xu & Carey, 2015;Klein et al, 2013;Lee et al, 2012), 2) Employee involvement in PE (e.g., Marie, 2016;Rivera & Landahl, 2019;Zampetakis & Moustakis, 2010), and 3) Determinants of PE (e.g., de Andrade et al, 2016;Gofen & Blomqvist, 2014;Zikou et al, 2017). Figure 6 reveals the number and percentage of the 61 PE articles that make up each category.…”
Section: Article Typementioning
confidence: 99%
“…The last theme amongst the PE themes is PE determinants (18%), whereby articles sought to understand the factors that determine whether or not a public sector organization adopted an entrepreneurial mindset. These factors were categorized into internal and external factors (Zikou et al, 2017). The internal factors included personal motivation and knowledge, while external factors included the level of economic activities and organization strategy and structure (e.g.…”
Section: Article Typementioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Pizzolato, as cited in Pérez (2014), affirmed that entrepreneurship can be understood as a productive activity that generates employment. Zikou et al (2018), however, highlighted the role of entrepreneurship as a driver for innovation, which may even be synonymous with innovation, creativity and new organisations. They argued that it is related to personal characteristics (skills and abilities), motivation and external environment aspects.…”
Section: Term Entrepreneurshipmentioning
confidence: 99%